A preventive multimodal analgesic strategy for bilateral rostral mandibulectomy in a horse. (30th September 2013) - Minghella, E.; Auckburally, A.
Summary This case report describes the use of a wound soaker catheter as part of a preventive multimodal analgesic plan in a mare undergoing a bilateral rostral mandibulectomy. The administration of local anaesthetic into the surgical wound using a wound soaker catheter, together with systemic nonsteroidal anti‐inflammatory drugs (NSAIDs) and opioid therapy, controlled post operative pain satisfactorily.